Hands-On Activity on Fine Motor Skills in Early Childhood Education - Sintia, Sintia; Romba, Sri Sufliati; Rahmat, M. Yusran (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Fine motor skills are a crucial aspect of early childhood education, which is a prerequisite for learning readiness but often requires effective and applicable learning strategies. Therefore, this study aims to test and determine the magnitude of the effect of the implementation of hands-on activity (direct practice activities) on the fine motor development of early childhood children in Early Childhood Education SPAS. Al-Kautsar Bontobiraeng. This study is quantitative with a pre-experimental approach using a one-group pretest-posttest design. The research subjects consisted of 10 children in group B (aged 5–6 years). The main data collection technique was observation using a checklist sheet based on indicators of children's fine motor development. Data was analyzed using the non-parametric Wilcoxon Signed Rank Test due to sample limitations. The results of the study showed a significant increase in children's fine motor ability scores after the intervention. The average pretest score was 20.4, increasing to 32.4 in the posttest. The results of the statistical test showed an Asymp. Sig. value (2-tailed) of 0.000, which is less than 0.05 (0.000 < 0.05). This finding indicates that there is a significant influence of the implementation of hands-on activity on the fine motor development of early childhood. This study provides a practical contribution: hands-on activity is proven to be effective in stimulating and improving children's fine motor skills through direct, fun, and meaningful learning experiences. These results can be a recommendation for early childhood education teachers to adopt direct practice activities in fine motor development stimulation programs.